Imposition of beneficial water stress for improvement of postharvest quality of lowland tomato fruits (Lycopersicon esculentum Mill.) - Nama, Mohammed Hassan (2018)
Water stress affects crop performance by influencing nutrient availability and crop functionality. There is a lack of information on utilization of deficit irrigation strategies in manipulating the growth rates, yield and quality of low land tomato plant in Malaysia. Present study was indicated to investigate the effects of different level of water stress on plant growth, yield and postharvest qualities. Two greenhouse experiments were conducted at Field 15, Faculty of Agriculture, Universiti Putra Malaysia. Experiment 1 was conducted to describe the effect of limiting strategically the water supply during plant development on plant growth, yield and postharvest quality, with the aim of identifying the best deficit schedule for the plants under low land tropical conditions. Three- week old MT1 tomato seedlings from the trays were transplanted into polybags filled with mixture of coco peat and paddy husk (2:1 V/V). After 40 days, the seedlings were treated with T1 control (daily watering to field capacity), T2 (restoring water supply to field capacity every two days) and T3 (restoring water supply to field capacity every four days). At harvest, plant height, leaves number, stem diameter, leaf area, dry shoot and root fresh and dry weight, fruit weight and fruit number were measured. In addition, data were collected on the following fruit quality parameters: firmness, total soluble solids, titratable acidity, pH, ascorbic acid and lycopene. The deficit irrigation applications increased soluble solids concentration significantly at T3 in the first experiment and at T4 (fruiting growth stage) in the second experiment. However, the rates of increment was not significantly different in titratable acidity, ascorbic acid, lycopene content, pH and firmness. The T2 (restoring water supply to field capacity every two days) promoted total fruit weight. Water stress treatments decreased plant heights, leaves number, leaf area, trusses number and both fresh and dry shoot and root weight. The leaf relative water content was reduced by 22.2% in the most stressed plants T3 (four days deficit irrigation) compared to the control. Whilst experiment 2 was conducted to identify the most critical phenological (plant growth stages) and fruit maturity stages to impose deficit irrigation and their effects on growth, yield and postharvest quality of tomato. Three weeks old seedlings were transplanted into polybags. Then, the seedlings were exposed to four water stress treatments: T1 (control), T2 (deficit irrigation every four days at the vegetative stage), T3 (deficit irrigation every four days at the flowering stage) and T4 (deficit irrigation every four days at the fruiting stage). All growth, yield and postharvest parameters were determined as in Experiment 1. The plants that subjected to deficit irrigation levels produced similar plant height and number of leaves to the control plants (full irrigation). However, fruit weight and number of fruit increased significantly under T3 (flowering stage) but not significantly different from those in control plants. In addition, water deficit irrigation at T4 (deficit imposed during fruiting stage) significantly reduced fresh and dry weight of shoots and root compared to the other treated and control plants. In conclusion, the optimum yield of tomato could be obtained at T3 (deficit imposed at flowering stage). The vegetative and flowering growth stages could be considered as the most tolerant to deficit irrigation, and the fruiting growth stage could be considered the most critical stage. Imposition water stress at flowering growth stage on tomato produced better plants condition, while using the water stress during fruiting stage retards plant growth by decreased plant growth and rate of yield. Fruits quality such as fruit firmness, pH of fruit, SSC, TA, AA and lycopene were affected significantly by deficit irrigation treatments. T4 (fruiting stage) fruits had the highest SSC in those harvested at the turning maturity fruit stage; high SSC improves both paste yield per unit of fresh fruit and overall processing efficiency. While the highest lycopene content was observed with those treated during vegetative stage harvested at the red maturity fruit stage. On the other hand, fruits harvested from T2 (vegetative stage) plants at turning maturity fruit stage gave the highest firmness. Highest pH fruit was obtained with T3 plants at red fruit maturity index. However, the results demonstrated that different deficit irrigation regimes did not affect TA and AA contents of tomato fruits, indicating that the results from of this study can enhance and maintaining post-harvest quality, also deficit irrigation strategy can help in the development of water management system for tomato production in the scenario of reduced water availability and enable the tomato growers to produce tomato with optimum yield by allowing little water stress without substantial yield reduction.